Private pensions and public policies - Gale, William G.; Shoven, John B.; Warshawsky, Mark (Brookings Institution Press, 2004)
The contributors to this volume assess the impact of policies and regulations and provide detailed analysis of specific components of the pension system, including taxation, Social Security reform, hybrid plans, pension guarantees, and nondiscrimination rules.